Diversion Effect of Economic Integration Agreements - Oanh, Nguyen Thi Hoang; Linh, Duong Thi Thuy (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2019)
Signing Economic Integration Agreements has proliferated during last three decades. A country signs more and more agreements. Owning the agreements not only generates trade creation but also trade diversion. The diversion effect of Economic Integration Agreements (EIAs) on the probability of products survival and export growth in a market is found in current paper. Using the probit function for 149 countries in SITC 4-digit level from 1962 to 2000, we find the hazard rate of product ceasing increases if a country signs any other EIAs other than its partner (both importer and exporter), and the export growth decreases in the case of an importer owns any other EIA other than its partner.